PENGEMBANGAN MODUL BERBASIS MASALAH UNTUK MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL PADA PEMBELAJARAN MATEMATIKA SISWA KELAS VIII MTsN TALAOK BAYANG KAB. PESISIR SELATAN - Aprilia, Dori - (STKIP PGRI Sumbar, 2014)
The background of the research is the studentâs difficulty in solving theproblem related to the daily life and lack of learning sources that are able to facilitatethe students to study independently. Therefore, to solve the problem, a problem-basedmodule for the material of the system of two-variable linear equation is developed.The research aims to develop a valid and practical problem-based module at MTsNTalaok Bayang. The validity result shows that the problem-based module developed isvery valid, i.e. 4.23 for the average and based on the practical questionnaire resultgiven to teachers and students are obtained a very practical category module in whichthe percentage is 90,90 % of the teacher and 90.30% of the students. Based on theresults, it can be concluded that the problem-based module for the material of thesystem of two-variable linear equation system in math learning to VIII grade studentsof MTsN Talaok Bayang is valid and practical.